Factors influencing the informal caregiving needs among the older adult population in Jiangmen City, China: a cross-sectional study - Zhou, Yue; Zhang, Huailei; He, Shan; Huang, Siqi; Zhang, Xin; Fu, Fang; Zhang, Guanghua (Frontiers in Public Health, 2025)
ObjectiveAlthough China has a vast population, less attention has been paid to the status and training needs of informal caregivers. This study aimed to assess the training needs of the informal caregivers in Jiangmen city, located in Guangdong Province in southern China.MethodsThree communities within a district of Jiangmen City were selected, and primary caregivers of older adults were invited to complete a self-developed training needs questionnaire. A total of 250 questionnaires were distributed, and 237 questionnaires were finally collected. Of the collected questionnaires, 214 (90.4%) were deemed valid.ResultsInformal caregivers reported a substantial caregiving burden. About 78.5% of informal caregivers had not received formal caregiving training, and over 91.1% expressed a need for such training. In terms of training content, the dimension of older adults care knowledge received the highest scores, followed by health care techniques and daily living care skills, while rehabilitation care techniques scored the lowest. The mean item score was 4.17 ± 0.88. Multi-stepwise regression analysis indicated that training needs of informal caregivers were significantly associated with age, education, employment status, and relationship to the care recipient.ConclusionThere is a strong demand for informal caregiver training in Jiangmen, Guangdong. Training needs were significantly associated with caregivers’ age, education, employment status, and relationship to the care recipient.